2017
DOI: 10.1053/j.gastro.2016.11.047
|View full text |Cite
|
Sign up to set email alerts
|

Daclatasvir Prevents Hepatitis C Virus Infectivity by Blocking Transfer of the Viral Genome to Assembly Sites

Abstract: In addition to inhibiting replication complex biogenesis, daclatasvir prevents viral assembly by blocking transfer of the viral genome to assembly sites. This leads to clustering of HCV proteins because viral particles and replication complex vesicles cannot form or egress. This dual mode of action of daclatasvir could explain its efficacy in blocking HCV replication in cultured cells and in treatment of patients with HCV infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 48 publications
4
36
0
Order By: Relevance
“…5C. Consistent with previous observations (6,23,40), the core proteins of wild-type JFH1 were largely coating LD (75% on LD, 5% on the ER, and 20% on LD and the ER), whereas the majority of the cells infected with the M21T mutant had core proteins either on the ER or on both the ER and LD (5% on LD, 30% on the ER, and 65% on LD and the ER), which was similar to the case with Jc1 (3% on LD, 71% on the ER, and 26% on LD and the ER). These results demonstrated that the M21T mutation altered the subcellular localization of core from LD to the ER for successive virion assembly processes.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…5C. Consistent with previous observations (6,23,40), the core proteins of wild-type JFH1 were largely coating LD (75% on LD, 5% on the ER, and 20% on LD and the ER), whereas the majority of the cells infected with the M21T mutant had core proteins either on the ER or on both the ER and LD (5% on LD, 30% on the ER, and 65% on LD and the ER), which was similar to the case with Jc1 (3% on LD, 71% on the ER, and 26% on LD and the ER). These results demonstrated that the M21T mutation altered the subcellular localization of core from LD to the ER for successive virion assembly processes.…”
Section: Resultssupporting
confidence: 92%
“…The nascent HCV RNA genomes are encapsidated by core proteins on lipid droplets (LD), and the resulting nucleocapsids are then translocated to the ER for budding. Previous work showed that HCV virion assembly rate was linked to the subcellular localization of the core (6,23,40). The Jc1 strain, whose core proteins are located on the ER, has more efficient virion assembly than the JFH1 strain, whose core proteins are mostly located on LD.…”
Section: Resultsmentioning
confidence: 99%
“…Wildtype NS5A positive punctae were on average smaller (peak 0.09-0.12 μm 2 ) than those in infected cells, however the S225A mutant exhibited significantly condensed and larger punctae (peak 0.18-0.21 μm 2 ). It has been reported that treatment of HCV-infected cells with the NS5A inhibitor DCV resulted in a perinuclear accumulation of NS5A (13), reminiscent of that observed for the S225A mutant. We therefore treated wildtype SGR harbouring cells with DCV and analysed the distribution of total NS5A and pS225-NS5A by ExM (Fig 10C).…”
Section: Resultsmentioning
confidence: 83%
“…DAAs target NS3/4A protease, NS5A, and NS5B RNA-dependent RNA polymerase, revolutionising HCV therapy (11). Daclatasvir (DCV) exemplifies a class of DAAs proposed to be potent inhibitors of NS5A (12, 13). However, the mode(s) of action for these compounds remains obscure as it is not clear which of the myriad functions of NS5A are inhibited.…”
Section: Introductionmentioning
confidence: 99%
“…By using an HCV replicase surrogate system, Berger et al demonstrated that DCV blocks the early biogenesis of the viral membranous replication factories (19). In addition, DCV blocks transfer of viral genome to the assembly sites to affect virion assembly (20).…”
Section: Introductionmentioning
confidence: 99%